Efficacy and safety of low-dose clopidogrel in Japanese patients after drug-eluting stent implantation: a randomized pilot trial - Ohkubo, Kenji; Fujimoto, Yoshihide; Iwata, Yo; Kitahara, Hideki; Kadohira, Tadayuki; Sugimoto, Kazumasa; Morino, Tomoki; Kobayashi, Yoshio (Heart and vessels, 2014)
In Japan, a lower maintenance dose of ticlopidine is used than in the United States and Europe. Therefore a lower maintenance dose of clopidogrel may also be considered appropriate in Japanese patients. The present randomized pilot study evaluated the efficacy and safety of 50 mg clopidogrel in Japanese patients who underwent drug-eluting stent (DES) implantation. A total of 200 patients with 277 lesions who underwent intravascular ultrasound-guided DES implantation were enrolled. The subjects were allocated to the 50- or 75-mg clopidogrel group. All patients received 100 mg aspirin daily before the procedure, and this continued indefinitely. The duration of clinical follow-up was 21.8 ± 5.7 months in the 75-mg group and 21.9 ± 6.1 months in the 50-mg group ( P = 0.96). During follow-up, no cardiac death, myocardial infarction, or stent thrombosis was observed in either group. Side effects of clopidogrel were observed in 4 patients (4.0 %) in the 75-mg group and in 4 patients (4.0 %) in the 50-mg group. Following this randomized pilot study, it may be justified to perform a large-scale randomized study comparing 50- and 75-mg dosing of clopidogrel in Japanese patients undergoing coronary stent implantation.